Kriminologi: Budaya dan Dinamika Penegakan Hukum di Masyarakat Multikultural - Fauziah, Hamidah Ulfa; Prayoga, Moh. Dwi; Rista, Diana; Andyastuti, Etty; Sasmita, Wikan; Mahendra, Azra'i; Sekarsari, Peni; Riswandi, Fitta Nurisma (CV. Kurnia Grup, 2025)
Criminology plays a crucial role in multicultural societies characterized by ethnic, cultural, and value-based diversity. In this context, criminology not only addresses the factors influencing criminal behavior but also explores how culture shapes perceptions of crime and law enforcement. This article investigates how criminology can provide deep insights into cultural dynamics within law enforcement practices, as well as the challenges and prospects for the future. The study emphasizes the importance of inclusive and culturally responsive law enforcement strategies and proposes the integration of criminology and cultural anthropology to develop policies that take local values into account. Such integration is expected to strengthen social and legal justice in increasingly complex societies. The data collection method used in this study is a literature review, which involves gathering and analyzing relevant works by previous researchers whose studies relate closely to the issues discussed.